Leader and Organizational Behavioral Integrity and Follower Behavioral Outcomes: The Role of Identification Processes - Ete, Ziya; Epitropaki, Olga; Zhou, Qin; Graham, Les (Journal of Business Ethics, 2022)
This paper investigates the concept of behavioral integrity from three important foci in organizational settings: i.e., leader, organization and follower. Drawing from theories of behavioral integrity, social learning and social identity, we examine the effects of leader and organizational behavioral integrity on follower behavioral integrity and organizational citizenship behavior via follower identification with leader and with organization, respectively. To test our hypotheses, we used data from three studies. Studies 1 and 2 were online experiments (N=211 and N= 200, respectively) in which behavioral integrity was manipulated in written scenarios to explore the proposed causal relationships. Study 3 was a multi-source field study that tested a mediation model using matched data collected from 280 employees and their co-workers from a Fire and Rescue Service in the United Kingdom. The findings provide partial support for our hypothesized model and highlight the importance of examining multiple foci of behavioral integrity as well as the role of follower identification as key mediating mechanisms of the relationship between leader and organizational behavioral integrity and follower behavioral outcomes. Theoretical and practical implications are discussed.
EPrint Processing Status: Full text deposited in DRO